Laparoscopic Sleeve Gastrectomy: A Radiological Guide to Common Postsurgical Failure. Issue 2 (May 2018) - Garofalo, Fabio; Pescarus, Radu; Denis, Ronald; Atlas, Henri; Garneau, Pierre; Philie, Michel; Sayegh, Karl
Laparoscopic sleeve gastrectomy is one of the most common bariatric procedures worldwide. It has recently gained in popularity because of a low complication rate, satisfactory resolution of comorbidities, and excellent weight loss outcome. This article reviews the surgical technique, expected postsurgical imaging appearance, and imaging findings of common complications after laparoscopic sleeve gastrectomy. Understanding of the surgical technique of laparoscopic sleeve gastrectomy and of the normal postsurgical anatomy allows accurate interpretation of imaging findings in cases of insufficient weight loss, weight regain, and postsurgical complications.